Developing a repeat sales index : home prices in San Diego, California - Das, Prashant; Sah, Vivek (London : Indian Institute of Management, Ahmedabad, 2024)
Bella Lopez, a data analytics entrepreneur and real estate asset management advisor is not satisfied with the standard real estate market indices available with her. She has access to a large amount of housing transactions data and considers developing her own house price indices at a more granular geographic level. She applies her data analytics skills to pursue these goals. Her intent is to build her firm’s thought leadership by developing indices more relevant to local areas.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Housing -- Prices -- Califoria -- Case studies; Real estate busines -- California -- Case studies